Water use and drought resistance of turfgrass and ornamental landscape plant species - Domenghini, Jacob Cody (Kansas State University, 2012)
In 2005, turfgrass was estimated to cover approximately 20 million ha of urbanized land. That area is increasing with rapid urbanization, stressing the importance of water conservation in the lawn and landscape industry. Turfgrasses have been identified for replacement by presumably more water-efficient ornamental plant species to conserve water. However, research comparing drought resistance and evapotranspiration (ET) of turfgrasses with ornamental landscape plants is limited. Two studies were conducted to evaluate water use and performance under drought stress of several ornamental and turfgrass species. An online course was developed to educate students about critical water issues related to irrigation in urbanizing watersheds. In a field study, ET was measured using lysimeters and plant water status was evaluated under deficit irrigation (100%, 60%, and 20% ET) in Festuca arundinacea Schreb., Buchloe dactyloides (Nutt.) Engelm. ‘Sharps Improved’, and Ajuga reptans L. ‘Bronze Beauty’. Evapotranspiration was similar between A. reptans and F. arundinacea, and was 32 and 35% greater than ET of B. dactyloides. In a greenhouse study, the performance of one turfgrass (Poa pratensis L. ‘Apollo’) and eight landscape species (Achillea millifolium L., Ajuga reptans L. ‘Bronze Beauty’, Liriope muscari Decne., Pachysandra terminalis Siebold and Zucc., Sedum album L., Thymus serpyllum L., Vinca major L., and Vinca minor L.) was evaluated during a severe dry down and subsequent recovery. S. album, L. muscari, and P. terminalis performed the best, requiring 86 to 254 d to decline to a quality rating of one (1-9 scale: 1=dead/dormant, 9=best quality). The remaining species required 52 to 63 d. The only species to recover were P. pratensis [46% pot cover (PC) after 60 days], S. album (38% PC), and V. major (35% PC). A survey was developed to measure student learning as it relates to the level of sense and meaning present in the content of a new online course entitled “Water Issues in the Lawn and Landscape.” Survey results were compared with student learning as measured through a post-test. Post-test scores declined as the difference between sense and meaning increased (r =-0.82; P=0.03), indicating student learning is higher when both sense and meaning are present.
Keywords: Turfgrass; Ornamental landscape species; Evapotranspiration (ET); Drought stress; Student learning; Sense and meaning; Horticulture (0471)